PENGARUH LOYALITAS KERJA, ETOS KERJA, DAN KUALITAS KERJA TERHADAP PRESTASI KERJA KARYAWAN PADA PT PEGATRON TECHNOLOGY INDONESIA - Siagian, Delpiana; Nasruji (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
This study aims to determine the significant simultaneous and partial relationship between work loyalty, work ethic and work quality as independent variables on employee performance as the dependent variable at PT Pegatron Technology Indonesia. This study used 101 respondents who were employees of PT Pegatron Technology Indonesia and were given questions in the form of a questionnaire. The study used a random sampling technique and used the slovin formula with a population of 136 people, and used SPSS 25 to process the collected data. As a result, the R2 is 0.524, which means that the work performance described in Work Loyalty, Work Ethics and Work Quality is 52.4% while the rest outside of other variables not examined is 47.6%. Work Loyalty, Work Ethic and Work Quality simultaneously have a significant effect on Employee Performance at PT Pegatron Technology Indonesia. Because it is explained that the sig value is 0.000 <0.05 with Fcount 15.482> Ftable 2.69.